MOLECULAR DIAGNOSTICSFOR THE POTATO SPINDLE TUBER VIROID IN THE REPUBLIC OF KAZAKHSTAN - Nadirova , L.T.; Stanbekova , G.E.; Beisenov , D.K.; Iskakov , B.K. (Eurasian Journal of Applied Biotechnology, 2016)
Potato is one of the most consumed crop products. It is grown inan area of 190000 hectares in Kazakhstan. The potato spindle tuber viroid (PSTVd) is the causative agent of the so-called ‘gothic’ disease, and it causesthe degradation of potato tubers anda decrease in yield of up to 65%. PSTVd has been found in every continent;in Kazakhstan, molecular diagnostics for PSTVd have not yet been performed. The first survey of PSTVd in Kazakhstan was performed, and spindle- and pear-shaped tubers collected from private farms in the Almaty region were grown under greenhouse conditions. Total RNAwas isolated from the leaves and analysed for the presence of PSTVd. Reverse transcription-polymerase chain reaction (RT-PCR) with specific primers revealed a 360-bp DNA fragment in a number of samples. The correspondence to PSTVd was confirmed using sequencing. Subsequently, the isolated PSTVd clone was used as a labelled probe for detecting the viroid in other plants. RT-PCR and nucleic acid hybridization assay revealed the presence of PSTVd in 26% of the selected spindle tubers. Currently, there are no effective methods to prevent the infection of potatoes by PSTVd; therefore, diagnostic methods are crucial for preventing the spread of PSTVd through seed material.